Larger Stimuli Require Longer Processing Time for Perception. (May 2017) - Kanai, Ryota; Dalmaijer, Edwin S.; Sherman, Maxine T.; Kawakita, Genji; Paffen, Chris L. E.
The time it takes for a stimulus to reach awareness is often assessed by measuring reaction times (RTs) or by a temporal order judgement (TOJ) task in which perceived timing is compared against a reference stimulus. Dissociations of RT and TOJ have been reported earlier in which increases in stimulus intensity such as luminance intensity results in a decrease of RT, whereas perceived perceptual latency in a TOJ task is affected to a lesser degree. Here, we report that a simple manipulation of stimulus size has stronger effects on perceptual latency measured by TOJ than on motor latency measured by RT tasks. When participants were asked to respond to the appearance of a simple stimulus such as a luminance blob, the perceptual latency measured against a standard reference stimulus was up to 40 ms longer for a larger stimulus. In other words, the smaller stimulus was perceived to occur earlier than the larger one. RT on the other hand was hardly affected by size. The TOJ results were further replicated in a simultaneity judgement task, suggesting that the effects of size are not due to TOJ-specific response biases but more likely reflect an effect on perceived timing.